Pelatihan Penulisan Karya Ilmiah pada Mahasiswa TPK untuk Terampil dan Kreatif Menulis - Lely Pramesti; Abdul Gafur; Rafly Ibrahim (Cv. Utility Project Solution, 2023)
Scientific paper writing training activities aim to provide knowledge on how to write scientific papers, motivate students to be skilled at writing and improve the quality of scientific papers for TPK students. The methods used in this training are lectures, questions and answers, discussions and case studies delivered online. After participating in this training, the participants have understood the material about the importance of writing, forms of scientific papers, basic format and how to write scientific papers, how to determine topics, titles, make frameworks and scientific papers. Participants are also taught how to manage references, conduct literature reviews and analyze research results. The results of this training provided knowledge to TPK students, around 90% of them were able to answer correctly all the questions on the simple instruments that were distributed. In addition, the participants seemed enthusiastic to know and explore the material presented. They also actively asked questions during the training. From these results it shows that the training objectives can be achieved, knowledge about scientific writing increases and motivation to write scientific papers begins to build as can be seen from the enthusiasm. So that after the training, it is hoped that many PKM scientific papers and other scientific papers can be produced, as well as the final project written to be more original and of higher quality.